Influencia de la pitahaya roja (Hylocereus undatus) liofilizada y lactosuero en las propiedades fisicoquímicas, antioxidantes y sensoriales de una bebida fermentada - Díaz Campozano, Edison Geovanny (2020)
The present research aimed to evaluate the influence of freeze-dried pitahaya pulp (Hylocereus undatus), and sweet whey on the physicochemical and functional characteristics of a fermented milk drink. Two concentrations of sweet whey (55 and 60%) and three percentages of lyophilized pitahaya (1, 1.5 and 2%) were applied; six treatments were obtained with experimental units of 2Kg and they were replicated by three, the formulated drinks underwent physicochemical analyzes (pH, acidity, total soluble solids and viscosity), total phenols (Folin-Ciocalteu) and antioxidant activity (ABTS method) at 0 and 15 days after preparation, at the end of storage, acceptability was evaluated with 50 untrained panelists, applying the Friedman test; these parameters were processed using the free program SPSS version 21. The freeze-dried pitahaya pulp at 2% showed a positive influence by improving the physicochemical characteristics of the drink, the sweet whey did not modify the characteristics except for the soluble solids; It was possible to show that the drink with 2% lyophilized pitahaya presented the highest content of phenols and the best antioxidant activity, in addition to the minimal loss of these properties over time due to the freeze-drying of the fruit; the drink proved to have adequate acceptance among untrained judges and to meet the physicochemical requirements of the NTE INEN 2337: 2008.